Left Ventricular T-Cell Recruitment Contributes to the Pathogenesis of Heart Failure. (July 2015) - Nevers, Tania; Salvador, Ane M.; Grodecki-Pena, Anna; Knapp, Andrew; Velázquez, Francisco; Aronovitz, Mark; Kapur, Navin K.; Karas, Richard H.; Blanton, Robert M.; Alcaide, Pilar
<x xml:space="preserve">Abstract</x> Background— Despite the emerging association between heart failure (HF) and inflammation, the role of T cells, major players in chronic inflammation, has only recently begun to be explored. Whether T-cell recruitment to the left ventricle (LV) participates in the development of HF requires further investigation to identify novel mechanisms that may serve for the design of alternative therapeutic interventions. Methods and Results— Real-time videomicroscopy of T cells from nonischemic HF patients or from mice with HF induced by transverse aortic constriction revealed enhanced adhesion to activated vascular endothelial cells under flow conditions in vitro compared with T cells from healthy subjects or sham mice. T cells in the mediastinal lymph nodes and the intramyocardial endothelium were both activated in response to transverse aortic constriction and the kinetics of LV T-cell infiltration was directly associated with the development of systolic dysfunction. In response to transverse aortic constriction, T cell–deficient mice (T-cell receptor, TCRα−/−) had preserved LV systolic and diastolic function, reduced LV fibrosis, hypertrophy and inflammation, and improved survival compared with wild-type mice. Furthermore, T-cell depletion in wild-type mice after transverse aortic constriction prevented HF. Conclusions— T cells are major contributors to nonischemic HF. Their activation combined with the activation of the LV endothelium results in LV T-cell infiltration negatively contributing to HF progression through mechanisms involving cytokine release and induction of cardiac fibrosis and hypertrophy. Reduction of T-cell infiltration is thus identified as a novel translational target in HF.